THE INFLUENCE OF ASWAJA TEACHING AND THE SPIRIT OF NATIONALISM ON THE KHILAFAH MOVEMENT IN ISLAM THROUGH SELF-AWARENESS - Asy’ Ary, Hasim; Nikmah, Khoirun; Daryono, Rihab Wit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Self-awareness helps individuals to appreciate diversity in religious thought and practice. Meanwhile, in the spirit of nationalism, this means being able to respect different national identities and interests without demeaning or ignoring religious beliefs. This research raises the urgency of understanding the teachings of Ahlussunnah wal Jama'ah (Aswaja) and the spirit of nationalism in the context of facing the caliphate movement in Islam, as well as the mediating role of self-awareness in these dynamics. The research aims to understand how Aswaja teachings and the spirit of nationalism influenced the caliphate movement, as well as how self-awareness mediates the influence of both. The research method uses a quantitative approach with a survey method, involving 97 students from Ma Ma'arif Nahdlatul Ummah using a stratified random sampling technique. The data collection technique was carried out through the use of a questionnaire with a Likert scale. Data analysis uses descriptive and inferential statistical analysis. The research results show that Aswaja teachings and the spirit of nationalism influenced the caliphate movement, with self-awareness mediating the influence of both. The implications of this research are important for developing strategies to prevent radicalization and extremism, as well as strengthening interreligious and intercultural dialogue. Recommendations include developing educational programs that promote the values of tolerance and pluralism, as well as involving religious leaders and community leaders in these efforts.